INTEGRASI ETNOSAINS DALAM PEMBELAJARAN IPAS UNTUK MENUMBUHKAN NILAI NASIONALISME - Binti Sholikhah, Widya; Anggraeni Siwi, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning in elementary education requires contextual approaches that connect scientific concepts with students’ real-life experiences. However, Integrated Science (IPAS) learning in many schools remains abstract and less effective in fostering conceptual understanding and character development, particularly nationalism values. This study aims to describe the implementation of ethnoscience integration in IPAS learning and its impact on fostering nationalism among elementary students. A qualitative descriptive approach with a case study design was conducted in a fourth-grade classroom at SD Negeri Joho 01 Sukoharjo, Indonesia. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that ethnoscience integration through contextual activities, such as industrial visits to traditional herbal medicine production and hands-on local product practices, significantly enhances students’ conceptual understanding of energy transformation and matter changes. Furthermore, it improves student engagement, learning motivation, and nationalism values, as reflected in their appreciation of local products, cooperation, and cultural pride. These findings suggest that ethnoscience-based learning serves as an effective and meaningful strategy to support contextual learning and strengthen character education within the Merdeka Curriculum.